Avaliação da atividade antiulcerogênica, antiinflamatória intestinal e antidiarreica da espécie Hyptis suaveolens (L.) Poit. (Lamiaceae) em modelos animais. - Machado, Flávia Danniele Frota (2016)
Hyptis suaveolens L. Poit. (Lamiaceae) is used in the treatment of gastric problems and inflammation. This study aimed to evaluate the duodenal anti-ulcer, intestinal antiinflammatory and anti-diarrheal activity of the crude ethanol extract (EtOHE-Hs) and the hexane phase (HexFa-Hs) obtained from aerial parts of Hyptis suaveolens. In the duodenal ulcer model induced by cysteamine, the EtOHE-Hs (31.25, 62.5, 125 mg/kg) and lansoprazole (30 mg/kg) reduced the ALU in 47, 61, 42 and 59% (p<0,001), respectively, while HexFa-Hs (31.25, 62.5, 125 and 250 mg/kg) and lansoprazole (30 mg/kg) reduced this parameter in 79, 84, 89, 72 and 58%, when compared to the respective negative control group. In the model of acute ulcerative colitis induced by TNBS the EtOHE-Hs (31.25, 62.5, 125 mg/kg) and prednisolone (2 mg/kg) significantly reduced the in ALU 63 (p<0,001), 76 (p<0,001), 32 (p<0,05) and 74% (p<0,001), and the lesion score to 5 (4-8); p<0.05, 4 (3-5); p<0.01 and 5 (2-8); p<0.05, both compared to their respective colitics groups. Besides, the HexFa-Hs (62.5, 125 mg/kg) and prednisolone (2 mg/kg) reduced the ALU in 50, 55 and 56% (both p<0.001 and the lesion score 5 (4-7), 5 (4-5) and 5 (4-6) (both p<0.01) when compared to their respective colitics groups. In the chronic model of ulcerative colitis induced by TNBS, the EtOHE-Hs (62.5 mg/kg) did not promote this reduction in parameters, already HexFa-Hs (125 mg / kg) and prednisolone (2mg / kg) reduced the damage score for 2 (1-3); p <0.01 and 1 (1-4); p <0.001, the weight / length 139 ± 26 (p <0.001) and 139 ± 80 (p <0.001) and diarrhea to 61% (p <0.001) and 47% (p<0.001), respectively, compared to colitic group. In the acute model of ulcerative colitis the EtOHE-Hs (31.25, 62.5 mg/kg) and HexFa-Hs (125 mg / kg) increase the levels of reduced glutathione (GSH) compared to colítico group p <0.01, p <0.05 and p <0.001, respectively. In the chronic model of colitis the HexFa-Hs (125 mg / kg) significantly increased the GSH levels (p <0.001), catalase (p <0.001) and superoxide dismutase (p<0.01) reduced the levels of malondialdehyde (p <0.001) and nitrite / nitrate (p <0.05) and myeloperoxidase (p <0.001) compared to the respective values of the colitic group. The HexFa-Hs (125 mg / kg) reduce interleukin-1 beta levels (IL-1β) and tumor necrosis factor alpha (TNF-α), both with p <0.001 and increased levels of interleukin 10 (IL-10) p <0.001 compared to colíticos groups. In the model of diarrhea induced by castor oil, EtOHE-Hs (500 mg/kg), the HexFa-Hs (500 mg/kg) and loperamide (5 mg/kg) significantly reduced the evacuation index (EI) when compared to the negative control with p <0.01, p<0.01 and p <0.001, respectively. The HexFa-Hs (500 mg / kg) and loperamide significantly reduced gastric emptying and intestinal transit to 69% (p <0.001) and 47% (p <0.001), respectively, and 35% (p <0.001) and 21% (p <0.001) compared to the respective negative control. The antimotility activity FaHex-H involves nitric oxide share, KATP, cholinergic and adrenergic.